War and Peace: War Memories and Museums in Japan. Issue 12 (December 2013) - Allen, Matthew; Sakamoto, Rumi
Abstract How is war remembered in public places in Japan? The high profile 'peace' museums of Hiroshima and Nagasaki, and Yushukan, the museum that is attached to the Yasukuni Shrine in Tokyo, have dominated both the English and Japanese language literature about sites of remembrance since the 1990s. The thrust of much of the literature emphasises the divide between Japan's recognition of its place as a victim of atomic bombing in war, and its recognition or denial of its aggression in East and Southeast Asia. In the 21st century, other less well‐known public institutions in Japan (Chiran Peace Museum for Kamikaze Pilots, Shokeikan Museum for Wounded Soldiers, Showakan, Okinawa Prefectural Peace Park and Memorial Museum, and Himeyuri Memorial and Museum) have produced different perspectives of Japan's wartime history. By briefly examining these lesser‐known museums, we demonstrate how the concept of 'peace' has been recast in various ways to provide legitimating contexts in which to rehabilitate Japanese people's experiences during the war. This research suggests that beyond the binary of 'victim‐victimiser' analyses of Japanese war memory there is room for research in this field that recognises and engages the complexity of how Japan's controversial wartime past is presented in the Japanese public domain.